2021
DOI: 10.1364/ol.434069
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the spatial entanglement from laser modes analogous to quantum wave functions

Abstract: The Schmidt decomposition is exploited to study the spatial entanglement of laser transverse modes analogous to quantum Lissajous states. Based on the inverse Fourier transform, the stationary Lissajous state can be analytically derived as a coherent superposition of degenerate Hermite–Gaussian eigenmodes. With the derived stationary state, the Schmidt modes and the participation number N can be employed to evaluate the spatial localization and the quantum entanglement. The larger th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…It has been demonstrated that Lissajous geometric modes can be well generated from an off-axis diode-end-pumped Nd:YVO 4 laser. The detailed description for the experiment can be obtained from previous papers [14,40,41]. When a short laser crystal with length of 1~2 mm was used in experiment, the value of M was found to be greater than 300 by far.…”
Section: Experimental and Numerical Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been demonstrated that Lissajous geometric modes can be well generated from an off-axis diode-end-pumped Nd:YVO 4 laser. The detailed description for the experiment can be obtained from previous papers [14,40,41]. When a short laser crystal with length of 1~2 mm was used in experiment, the value of M was found to be greater than 300 by far.…”
Section: Experimental and Numerical Resultsmentioning
confidence: 99%
“…for the new degeneracy of ( , ) p q can be obtained from Equation (33) as with z R,x and z R,y , the beam waists are w o,x = λz R,x /π and w o,y = λz R,y /π, where λ is the laser wavelength. In terms of ∆ f T,x , ∆ f T,y , z R,x and z R,y , the parametric equations for an astigmatic cavity can be derived as [18,41] x s (z) = √…”
Section: Parametric Equations For Lissajous Geometric Raysmentioning
confidence: 99%
See 2 more Smart Citations
“…It is not surprising that SML lasers exhibit more complex transverse dynamics since SML is inherently a nonlinear phenomenon, and 'soft aperture' is the only mechanism to limit higher-order transverse modes. For example, the Lissajous geometric mode derived by Chen et al [11,12] using SU(2) quantum theory, is the superposition of different orders of Hermite-Gaussian(HG) modes and different longitudinal modes.…”
Section: Introductionmentioning
confidence: 99%